2022
DOI: 10.3389/fnins.2021.791964
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture Reduces the Risk of Dysphagia in Stroke Patients: A Propensity Score-Matched Cohort Study

Abstract: Background: Post-stroke dysphagia (PSD) affects the quality of life in stroke patients, impairs their rehabilitation ability, and causes other complications following stroke. Currently, there is currently some understanding of PSD risk factors, but its protective factors remain largely unknown.Objective: To analyze the effects of acupuncture (AP) on dysphagia in stroke patients and explore its potential as a preventive therapy.Methods: Patients with a diagnosis of stroke from 2010 to 2019 were selected and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Treatment and nursing care of patients with dysphagia after stroke is a holistic process from swallowing assessment to rehabilitation, emphasizing multidisciplinary participation and comprehensive training [ 37 39 ]. The assessment of dysphagia after stroke should be based on the clinical manifestations of patients, and fully consider the advantages of assessment methods, so as to improve the accuracy and effectiveness of dysphagia screening and treatment [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment and nursing care of patients with dysphagia after stroke is a holistic process from swallowing assessment to rehabilitation, emphasizing multidisciplinary participation and comprehensive training [ 37 39 ]. The assessment of dysphagia after stroke should be based on the clinical manifestations of patients, and fully consider the advantages of assessment methods, so as to improve the accuracy and effectiveness of dysphagia screening and treatment [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The report indicates that patients with infratentorial strokes had worse swallowing functions compared to those with supratentorial strokes. However, a single-center retrospective study showed that the risk of PSD was reduced in patients receiving acupuncture treatment, regardless of whether the stroke occurred in the brainstem [adjusted hazard ratio (AHR) = 0.41], thalamus (AHR = 0.13), or was a multifocal lesion (AHR = 0.40) (57). Although the results indicate that acupuncture treatment can reduce the risk of dysphagia in stroke patients across various demographics, including different ages, sexes, stroke types, sites, and baseline comorbidities (57), we recognize the need to further elucidate the application of acupuncture techniques in diverse clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that acupuncture may repair the connections between the upper motor neurons and motor nuclei of the medulla oblongata [25] . Another propensity score-matched cohort study matched 3,618 patients with IS between 2010 and 2020 using acupuncture and non-acupuncture and showed that acupuncture treatment reduced the risk of dysphagia in stroke patients [109,118] . Unfortunately, this was a single-center study, and follow-up is pending.…”
Section: Acupuncture Promotes the Recovery Of Dysphagia And Reduces T...mentioning
confidence: 99%